"Sowing and Growing" Life Skills Through Garden-Based Learning to Reengage Disengaged Youth (LEARNing Landscapes, 2016)
There is an emerging body of literature that explores the impact of garden-based learning on health, well-being, social cohesion, and educational outcomes. In this paper, we examine a pilot study conducted in partnership with the Royal Botanic Gardens’ Youth Community Greening to implement a gardening program with disengaged youth. Data was collected through eldwork and semi-structured interviews, revealing ve interconnected themes: enhancing well-being and health literacy; building life skills; engaging students; connecting with adults; and increasing self- esteem. We conclude by showcasing some of the collaborative practices between educational contexts and communities to reveal how these partnerships can be mutually enhancing.
Keywords: garden-based learning; health; well-being; social cohesion; youth; community; educational outcomes; self-esteem